UPAYA PENINGKATAN AKTIVITAS BELAJAR MAHASISWA PRODI PENDIDIKAN BIOLOGI MENGGUNAKAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) PADA MATA KULIAH KIMIA DASAR - Haris Munandar (Lantanida Journal, 2018)
General chemistry is a subject that being studied in almost every science course. The subject is closely related to the environment, so it will be very easy to learn when involve examples in everyday life. The Contextual Teaching and Learning (CTL) approach is an approach that links the learning materials with the real-world environment. This research was conducted by using a CTL approach in a general chemistry subject which is one of the compulsory subjects in Biology Education Program of Tarbiyah Faculty UIN Ar-Raniry. The aim of this study was to determine the increase of student learning activities after using the CTL approach to general chemistry lecturing activities. The design of this study used action classroom research. This study was conducted to the first semester students. The student amount was 31 students. The instrument used was an observation sheet of learning activity. The results was obtained that the activities of the student during the learning process in the first cycle reached 70% and increased to 90% in cycle II. This proves that the application of CTL approach can increase the learning student’s activity of Biology Education Studies in general chemistry courses.